(3GdedJbW ef TQM GdhGMOi dTYQ GdeJfHis - (3CHh GdbGSe , eMehO Hf YeQ GdReNTQis; (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj,J (B468 (3g` s ((3eMeO Hf GdNVQ GdCfUGQi GdehUdi s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdReNTQi QVi Gddg Yfg (B: (3gPG eG GdJbWJg ef TQM TYQ CHj GdWjH Yf GdhGMOi s
(3BNQgG (B:s
(3BNQ eG TGJed Ydjg OjhGfg GdPi QJHg HfaSg NeSI Cda hCQHY eGCjg hGQHYI hJSYjf bGajI Je GdedJbW ef TYQ GdeJfHi s
(3UaMI GdYfhGf ePgHIs
(3hQO GdYfhGf GdCUdi ai cX (B1/ 809s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B26 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B692s
Keywords: (3GdCOHs